Factors That Influence Stock Market Volatility: A Case Study From Malaysia - Dety Nurfadilah; Sudarmawan Samidi (International Journal of Business Studies, 2018)
The purpose of this study is to investigate to what extent earning per share, net income, dividends and sharia compliance affects the stock market volatility in Malaysia. A sample of 53 firms has been selected from FBM KLCI for the period of 2014 when the oil price decline over 55% and leads to lower share prices. Multiple regression methods have been applied to the data. The result found that earning per share and dividend have a strong signiicant relationship, while net income and Shari'ahcompliance are not signiicance towards stock price volatility. It is hoped that the outcomes of this study will serve as the reference for the investor and manager to create better and effective strategy, as well as, to improve the inancial market industry